PRODUCTION OF ALKALINE PROTEASE FROM A THERMOALKALOPHILIC BACILLUS SP.JB-99 UNDER SOLID STATE FERMENTATION - SHIVASHARANA C.T; G.R.NAIK (International Journal of Pharma and Bio Sciences, 2012)
The production of extracellular thermostable alkaline protease by a thermoalkalophlic Bacillus sp. JB-99 under solid state fermentation was investigated using various agro wastes as inexpensive solid substrate raw materials. Physical and chemical parameters were optimized. Wheat bran was found as a cheap and chief source of solid substrate to yield maximum amount of alkaline protease (7222 U/g) under the optimum conditions: moisture content at the ratio of 1:2.0 (w/v); Mineral Salt solution (MS1); pH of the medium (10.0) using separately sterilized Na2CO3 solution; inoculam concentration of 15% (v/w); incubation temperature at 50oC under 90-95% relative humidity (provided by sterile distilled water) and 96hours of fermentation. Wheat bran in combination with Sugarcane bagasse showed comparatively better yield of enzyme. Carbon additives like Arabinose, Citric acid, Raffinose, Starch and Fructose; organic nitrogen sources (Casein and yeast extract) and inorganic nitrogen (NaNO3 and KNO3)improved the enzyme yield, whereas Galactose, Lactose and Glycerol were minimized, but Dextrose, NH4NO3 and NH4Cl were strangely inhibited. The Glucose supplementation has totally repressed the alkaline protease production. This investigation could, therefore, lead to substantial reduction in the overall cost of enzyme production compared to submerged fermentation.